2011
DOI: 10.1186/1472-6963-11-154
|View full text |Cite
|
Sign up to set email alerts
|

Providing medical care for undocumented migrants in Denmark: what are the challenges for health professionals?

Abstract: BackgroundThe rights of undocumented migrants are frequently overlooked. Denmark has ratified several international conventions recognizing the right to health care for all human beings, but has very scanty legislation and no existing policies for providing health care to undocumented migrants. This study focuses on how health professionals navigate and how they experience providing treatment for undocumented migrants in the Danish health care system.MethodsThe study was carried out as part of an EU-project on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 15 publications
(21 reference statements)
3
43
0
1
Order By: Relevance
“…Good coordination of mental, physical and social care is essential to provide good care for refugees with complex health and social problems, many of whom may not access mental health services directly (McColl & Johnson, 2006;Jensen et al 2011;Dauvrin et al 2012). Yet, the fragmentation of health and social care services is a commonly reported concern in highincome countries (Giacco et al 2015).…”
Section: Overcoming Barriers To Carementioning
confidence: 99%
“…Good coordination of mental, physical and social care is essential to provide good care for refugees with complex health and social problems, many of whom may not access mental health services directly (McColl & Johnson, 2006;Jensen et al 2011;Dauvrin et al 2012). Yet, the fragmentation of health and social care services is a commonly reported concern in highincome countries (Giacco et al 2015).…”
Section: Overcoming Barriers To Carementioning
confidence: 99%
“…With the perceptions of healthcare professionals in mind, Priebe et al (2011) conducted a study to assess the difficulties experienced by professionals when providing care to migrants, and what they consider constitutes good practice to overcome these problems. Following structured interviews, eight types of problems and seven components of good practice were identified representing all statements in the interviews.…”
Section: Moving Forwardmentioning
confidence: 99%
“…The use of non-verbal cues offers another viable strategy for nurses. [5,16] The low levels of literacy of backstretch workers presents an added hurdle for nurses as they develop and disseminate health education materials, client instructions, and secure signed consents for screening and procedures. An additional problem arises for non-English speaking clients who experience low literacy levels, and need translation of health information.…”
Section: Nutritional Statusmentioning
confidence: 99%
“…Conversely, it was reported that practitioners articulated a concern for the added levels of stress migrant workers experienced during a client encounter as a consequence of not understanding the medical issue, and how the communication barrier prevented the practitioner from reassuring the client using a common language. [16] Several strategies to alleviate communication barriers include arranging for an interpreter, making use of a bilingual employee, and looking to the client's network of family, friends, or other contacts to interpret and convey health information. The use of non-verbal cues offers another viable strategy for nurses.…”
Section: Nutritional Statusmentioning
confidence: 99%
See 1 more Smart Citation